MULTIKULTURALISME DI PESANTREN: POTRET PENDIDIKAN ISLAM MULTIKULTURAL - Mursyid, Mursyid (Universitas Nurul Jadid, 2015)
This article portrays a process of multicultural education in Pesantren as a multicultural Islamic education. Islamic education, with its inclusive character, is a basic requirement of developing multiculturalism in Pesantren. A multicultural education is not merelly integrated to curriculum, but also embedded into an attitude of kiyai and ustadz as modeling figure in Pesantren tradition, making santri easily adaptable with multicultural values, and by doing so it finally creates an insight of nationalism in Pesantren.